Primary biliary cholangitis (PBC)-autoimmune hepatitis (AIH) variant syndrome: clinical features, response to therapy and long-term outcome - Graf, Markus; Lange, Christian; Langer, Mona M.; Schattenberg, Jörn Markus; Seeßle, Jessica; Dietz, Julia; Vermehren, Annika; Michael, Florian A.; Mondorf, Antonia; Zeuzem, Stefan; Pathil-Warth, Anita; Graf, Christiana (Journal of Clinical Medicine, 2023)
Introduction: Standardization of diagnostic criteria of autoimmune hepatitis (AIH) and primary biliary cholangitis (PBC) variant syndrome (AIH-PBC VS) has not been achieved so far and evidence-based recommendations for monitoring and treatment of the disease are still lacking. Our study aimed to assess the prevalence, biochemical, and serological features, as well as the clinical course, of VS. Methods: We performed a retrospective study including all patients with VS between 1999 and 2020 in four German centers. Data on demographic parameters, biochemical and serological tests, treatment, and outcome were collected. Results: Of 90 patients (3.1%) meeting Paris criteria for VS diagnosis, 65.6% showed AIH and PBC histological features, while biochemical Paris criteria were observed comparatively rarely. Further antibodies, which were not part of the diagnostic criteria of VS, were found in a subgroup of patients with available data (ACA: 30.0%; anti-CENP-A: 25.0%; anti-CENP-B: 33.3%; anti-SP100: 21.4%). Biochemical response was more frequently observed in patients treated with a combined therapy of ursodeoxycholic acid (UDCA) and immunosuppression (IS). Liver cirrhosis was detected in 31 patients (34.4%) and 25 patients (27.8%) developed clinical manifestations of portal hypertension. Conclusions: Biochemical Paris criteria of VS were rarely detected, thus implying that these cut-off values should be redefined. Regarding pharmacological treatment, combined therapy of UDCA and IS appeared to be more effective than monotherapy with UDCA.
Gesehen am 26.01.2024